2005
DOI: 10.1073/pnas.0508798102
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-driven decoupling of key phases of organic matter degradation in marine sediments

Abstract: The long-term burial of organic carbon in sediments results in the net accumulation of oxygen in the atmosphere, thereby mediating the redox state of the Earth's biosphere and atmosphere. Sediment microbial activity plays a major role in determining whether particulate organic carbon is recycled or buried. A diverse consortium of microorganisms that hydrolyze, ferment, and terminally oxidize organic compounds mediates anaerobic organic matter mineralization in anoxic sediments. Variable temperature regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 26 publications
7
88
0
Order By: Relevance
“…The accumulation of DOC resistant to transformation or uptake is also in accordance with observations of DOC generated in short experiments conducted with coastal temperate sediments (Weston and Joye, 2005). In that study, passage of artificial anoxic porewater through bioreactors filled with temperate sediments collected at different seasons and incubated at the in situ temperatures of 12-29°C yielded an outflow of DOC from the bioreactors.…”
Section: Carbon Cycling Under Changed Temperature Regimes: Evidence Osupporting
confidence: 66%
See 2 more Smart Citations
“…The accumulation of DOC resistant to transformation or uptake is also in accordance with observations of DOC generated in short experiments conducted with coastal temperate sediments (Weston and Joye, 2005). In that study, passage of artificial anoxic porewater through bioreactors filled with temperate sediments collected at different seasons and incubated at the in situ temperatures of 12-29°C yielded an outflow of DOC from the bioreactors.…”
Section: Carbon Cycling Under Changed Temperature Regimes: Evidence Osupporting
confidence: 66%
“…In Arctic sediments, substrate addition and/or homogenization also led to transient buildup of DOC constituents such as VFA (Brü chert and Arnosti, 2003;Arnosti et al, 2005), but within days to weeks, the accumulated DOC was consumed again. Short-term experiments with substrateamended coastal sediments also showed that production and consumption of DOC can become unbalanced over the temperature range typically experienced by temperate sediments (Weston and Joye, 2005).…”
Section: Carbon Cycling Under Changed Temperature Regimes: Evidence Omentioning
confidence: 99%
See 1 more Smart Citation
“…Values of CarbonNitrogen atomic ratio (C/N) suggests an organic matter input derived from vascular plants (Meyers, 1994), characterized by limiting nitrate concentration (Mari et al, 2001). The mean value of our study (C/N = 1.41 ± 0.34) is lower the Redfield ratio (C/N = 5.7; Gordon and Goni, 2004;Weston and Joye, 2005). The TN of the sediments avoids being remineralized into the water column by adsorption to the mineral clay surface, hence recording smaller C/N ratios (Stevenson and Cheng, 1972;Suthhof et al, 2000) that are explained by selective degradation of the organic compounds and by immobilization of N by microorganisms during early diagenesis (Meyers, 1994).…”
Section: Ajesmentioning
confidence: 92%
“…At the end of all incubations, sample fluid was frozen until subsequent dissolved organic carbon (DOC) and total dissolved nitrogen (TDN) analysis. DOC and TDN concentrations were measured in the Joye Geochemistry Analytical Laboratory at the University of Georgia (USA) according to published protocols (Weston and Joye, 2005). Briefly, 10 mL of fluid from the leaching experiments was transferred into acid-washed, combusted autosampler vials.…”
Section: Leaching Experimentsmentioning
confidence: 99%